Analysis of 100 Cases of Ascites: A Prospective Study - Aamir Hussain, Afroze Fatima, Shujee Ahmad, Muhammad Shuaib, Abdul Majid, Vijay Kumar Bhojwani (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the causes of ascites in adult patients Study design: A prospective study Place and duration. The study was carried out at Pakistan Air Force Hospital Faisal Base Karachi from January 2019 to October 2019. Patients and Methods: All patients with ascites both male and female were included in this study. A detailed medical history and complete examination were carried out. Ascites was confirmed by ultrasound and ascitic fluid was taken and sent to laboratory for different tests. Blood was sent for chemistry and cells count. Result: A total of 100 patients were enrolled. Out of them, 68 were male and 32 were female. Cirrhosis of liver was found in 66 patients, malignancy-related ascites in 14 patients, peritoneal tuberculosis in 12 patients, congestive cardiac failure in 5 and nephrotic syndrome was found in 3 patients. Conclusion: Liver cirrhosis was the leading cause of ascites in adult patients. Hepatitis C virus was mainly responsible for cirrhosis. Strict policy to cut down viral transmission can prevent hepatotropic virus related liver disease and ultimately its common complication ie ascites.